2021
DOI: 10.1029/2020pa003993
|View full text |Cite
|
Sign up to set email alerts
|

Loess‐Like Dust Appearance at 40 Ma in Central China

Abstract: During wintertime, the Asian continent is characterized by a high atmospheric pressure system developing over southern Siberia and Mongolia. This semi-permanent high-pressure system known as the Siberian High drives strong northwesterly winds of the modern-day East Asian winter monsoon bringing cold and dry air from the Asian interior (Chang et al., 2006). During springtime, the Siberian High creates a strong meridional temperature contrast between cold air in the north and warmer air in the lower mid-latitude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 126 publications
0
6
0
1
Order By: Relevance
“…To shed light on the hydroclimatic transition from relatively wet to dry climate at ∼47.6 Ma in the Linxia Basin, three main forcing mechanisms, namely, the eustatic cycle of the Paratethys Sea, the uplift of the Tibetan Plateau, and global cooling, have been proposed (e.g., Dupont‐Nivet et al., 2007; Fang et al., 2015; J. X. Li et al., 2018; Meijer et al., 2019, 2021; Song et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To shed light on the hydroclimatic transition from relatively wet to dry climate at ∼47.6 Ma in the Linxia Basin, three main forcing mechanisms, namely, the eustatic cycle of the Paratethys Sea, the uplift of the Tibetan Plateau, and global cooling, have been proposed (e.g., Dupont‐Nivet et al., 2007; Fang et al., 2015; J. X. Li et al., 2018; Meijer et al., 2019, 2021; Song et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from the Xorkol, Qaidam, and Xining Basins have also suggested that the role of the Paratethys Sea in hydrological cycles and silicate weathering rates in the NE Tibetan Plateau during the early‐middle Eocene was nonsignificant (Fang, Galy, et al., 2019; J. X. Li et al., 2018). The retreat of the Paratethys Sea from central Asia, which exerted a significant impact on paleoclimate change in the northern Tibetan Plateau, may not have occurred earlier than ∼40 Ma (R. E. Bosboom et al., 2014; R. Bosboom et al., 2014; Carrapa et al., 2015; J. X. Li et al., 2018; Meijer et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Peri-Tethys-Siberian (Turgay strait) and Siberian-Arctic (Kara strait) connections likewise show increased restriction around middle Eocene climatic optimum times (Palcu and Krijgsman, 2022). Interestingly, a shift to more arid conditions is recorded in dust records from central China at 40 Ma (Bosboom et al, 2014;Meijer et al, 2021), i.e., coincident with the middle Eocene climatic optimum, which Meijer et al (2021) related to a major Peri-Tethys regression from the Tarim and Tajik basins around 41-40 Ma (Kaya et al, 2019). We surmise that increased restriction and euxinia in the Kuma basin can be mechanistically related to the observed middle Eocene climatic optimum-associated cooling if boreal surface inflow, e.g., from the North Sea, became dominant over the southern gateways, thereby suppressing middle Eocene climatic optimum warmth (Palcu and Krijgsman, 2022).…”
Section: Basin Restriction and Deoxygenation Associated With The Midd...mentioning
confidence: 98%